2014
DOI: 10.1021/jo502036f
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for Metal Triflate Catalyzed Direct Glycosylations with GalNAc 1-OPiv Donors

Abstract: Herein we report on the development of novel glycosylation methodology for the concise synthesis of naturally occurring glycoconjugate motifs containing N-acetylgalactosamine (GalNAc) from the cheaper and commercially available N-acetylglucosamine (GlcNAc). The stereoselective glycosylations proceed with catalytic amounts of a promoter and without the need for N-protection other than the biologically relevant N-acetyl group. Among the catalysts explored, both Bi(OTf)3 and Fe(OTf)3 were found to be highly activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…It is well known that the solubility of acetamido-2-deoxysugars can be problematic in practice. 30 Octaacetyl lactose (12) gave similar results (1 1 / 2 h, 89%) as found for the monosaccharides described above.…”
supporting
confidence: 73%
“…It is well known that the solubility of acetamido-2-deoxysugars can be problematic in practice. 30 Octaacetyl lactose (12) gave similar results (1 1 / 2 h, 89%) as found for the monosaccharides described above.…”
supporting
confidence: 73%
“…It has also been demonstrated that catalytic amounts of triflic acid activated the β‐donors 1β and 88 for the glycosylation of the 6‐OH glycosidic acceptor 45 and octanol 77 , respectively (Scheme ).…”
Section: Disarmed Glycnac Donorsmentioning
confidence: 99%
“…Similar conditions were described for the activation of the GalNAc donor 88 bearing a pivaloyl group at the anomeric position . This donor 88 was easily synthesized from N ‐acetylglucosamine in three steps .…”
Section: Disarmed Glycnac Donorsmentioning
confidence: 99%
“…This method tolerates per‐benzylated glucal and a variety of alcohol acceptors. In addition, Fe(OTf) 3 was also reported as an effective Lewis acid catalyst for direct glycosylation of GalNAc 1‐ pivalate donors with alcohols to afford corresponding O ‐glycosides …”
Section: Synthesis Of O‐ N‐ and C‐glycosides And Glycosyl Bromidmentioning
confidence: 99%